X-ray scattering as a probe for warm dense mixtures and high-pressure miscibility - Wuensch, K; Vorberger, J; Gregori, G; Gericke, DO (2011)
We develop a new theoretical approach that demonstrates the abilities of elastic X-ray scattering to yield thermodynamic, structural, and mixing properties of dense matter with multiple ion species. The novel decomposition of the electron structure factor in multi-component systems provides the basis to study dense mixtures as found in giant gas planets or during inertial confinement fusion. We show that the scattering signal differs significantly between single species, microscopic mixtures, and phase-separated fluids. Thus, these different phases can be distinguished experimentally via elastic X-ray scattering. © 2011 Europhysics Letters Association.